Analysis of stem and root extract of kepok banana (musa paradisiaca Linn.) in inhibit staphylococcus aureus growth - Harlina Harlina; Octhavya PD. Pradana (Journal of Dentomaxillofacial Science, 2019)
Objective: To Determine the activity stems and roots of banana plants kepok in inhibiting the growth of Staphylococcus aureus.Material and Methods: The study is an experimental laboratory to design a post-test only controlgroup. Extract the stem and roots of kepok banana plants. Obtained by maceration using methanol. The extract Obtained each diluted into a concentration of 6:25%, 12.5% and 25%. DMSO 10% and distilled water as the diluent. Inhibition of the extract was tested by paper disc diffusion method on Mueller-Hinton media Agar. Major inhibitory stem and root extracts of kepok banana seen by the diameter of inhibition formed around the paper discs.Results:Â  The average diameter formed on the stem extract concentration of 6:25%, 12.5% and 25% respectively was 11, 17 mm, 9.86 mm and 9.72 mm. Root extract with a concentration of 6:25%, 12.5% and 25% respectively are 8:16 am, 7:36 and 7:43 mm mm. Retrieved p = 0.000 (P <0.05) for each of the stems and roots.Conclusion: Stem and roots of kepok banana plants had activity in inhibiting the growth of bacteria Staphylococcus aureus.